The Management and Outcomes of Stoma Care with Impaired Integrity: A Case Study - Antonio Fesarlo Carlos; Miciella Angela; Domenica Amelia Da Silva (Journal of Wound Research and Technology, 2024)
Background: Colostomy globally affects not only physical but also psychological aspects in patients, and has been done for various reasons such as cancers of the colon and rectum. Tissue integrity disorders, irritations, and pain come up and require close service to care by nursing interventions and education for these conditions, especially in old patients. Purpose: The goal of this study was to evaluate the management and outcomes of stoma care in patients after colostomy surgery who were seen with tissue integrity disorders. Methods: The case-study approach was implemented into two male patients aged 76 and 80 years who were diagnosed with proximal rectal cancer and were given double-barreled colostomy treatment at Vila Alpina Hospital in São Paulo. Nursing intervention was on stoma care during cleaning and monitoring stoma characteristics as well as educating patients and their families on stoma care. Data were collected and analyzed over 3 days, while evaluation of outcome was done at tissue integrity and pain levels. Results: After the intervention of 3 days, partial improvement in tissue integrity was observed. The physical condition of both patients with normal tissue perfusion, absence of infection signs or bleeding, and partial developmental progress was seen in stoma wound healing. In addition, pain reduction was observed from a level of 4 to 2. However, healing was not fully achieved within the study period because of its short observation time. Conclusion: Nursing care considering observation, education, and therapeutic interventions will have improved outcomes of stoma and will also alleviate pain in colostomy patients. Further interventions of care and education to the patient will follow up these conditions for a long time.